Daylight photodynamic therapy with methyl aminolevulinate cream is effective and nearly painless in treating actinic keratoses: a randomised, investigator‐blinded, controlled, phase III study throughout Europe. (5th October 2015) - Lacour, J‐P.; Ulrich, C.; Gilaberte, Y.; Von Felbert, V.; Basset‐Seguin, N.; Dreno, B.; Girard, C.; Redondo, P.; Serra‐Guillen, C.; Synnerstad, I.; Tarstedt, M.; Tsianakas, A.; et al.
Abstract: Background: Unmet needs exist in actinic keratosis (AK) treatment. Daylight photodynamic therapy (DL‐PDT) has shown good efficacy and safety results compared to conventional PDT (c‐PDT) in a recent Phase III multi‐centre randomised controlled trial in Australia among 100 subjects with AKs. Objectives: Demonstrate non‐inferior efficacy and superior safety of DL‐PDT compared to c‐PDT in treating multiple mild and/or moderate facial/scalp AKs. Methods: Phase III, 12 week, multi‐centre, randomised, investigator‐blinded, controlled, intra‐individual study conducted at different latitudes in Europe. AKs of adult subjects were treated once with methyl aminolevulinate (MAL) DL‐PDT on one side of the face and MAL c‐PDT contralaterally. Endpoints for DL‐PDT concerned efficacy (non‐inferiority regarding complete lesion response at week 12) and safety (superiority regarding subject's assessment of pain after treatment, on an 11‐point numeric rating scale). Safety evaluation also included incidence of adverse events. Subject satisfaction was described using a questionnaire at baseline and last visit. Results: At week 12, the total lesion complete response rate with DL‐PDT was similar (non‐inferior) to c‐PDT (70% vs. 74%, respectively; 95% CI [−9.5; 2.4] in PP analysis, confirmed in ITT analysis). In addition, efficacy of DL‐PDT was demonstrated regardless of weather conditions (sunny or cloudy). DL‐PDT was nearly painless compared to c‐PDT (0.7 vs. 4.4, respectively; P < 0.001), better tolerated and resulted in higher subject satisfaction. Conclusion: DL‐PDT in comparison with c‐PDT was as effective, better tolerated and nearly painless with high patient satisfaction, and may be considered a treatment of choice to meet needs of patients with mild or moderate facial/scalp AKs.